Supporting Polish-Ukraine: A case study on the Afrikaans churches" reaction to communism - Alten, Herman H. van (HTS teologiese studies, 2021)
This article explores the role of the Afrikaans sister churches during the initial stages of the fight against communism. After initially sketching the relations between South Africa and Russia until the Bolshevik Revolution of 1917, focus is placed on a narrow case of financial support from the side of the Reformed Church in South Africa (the GKSA) via the Reformed Churches in the Netherlands towards the reformed movement in Polish-Ukraine during the 1930s and 1940s. Through the use of primary sources, this small historical cross-section illustrates how the GKSA, in cooperation with the other Afrikaans churches, fought the battle against communism during these initial stages. It also highlights the motivations that drove them. The sources reveal that the GKSA was not only concerned about the Reformed movement in far-away Polish-Ukraine, but that there was also a healthy measure of self-preservation and self-interest involved, protecting South Africa and its Christian population from the influence of communism by subtly promoting Calvinism as a formative paradigm for Afrikaner nationalism.Contribution: This article contributes to a better understanding of the relations between Reformed Churches in South Africa and Eastern Europe during the first half of the 20th century, as well as to the role of the churches in fighting what it perceived as dangerous ideological influences.